Novelties in the treatment of heart failure - Stepanović-Petrović, Radica (Archives of Pharmacy, 2022)
Despite advances in the treatment of heart failure, mortality from this disease remains higher than for many cancers, including breast and prostate cancer. The greatest progress in the therapy of heart failure with reduced ejection fraction (HFrEF) has been achieved by the drugs that antagonize the neurohumoral response to heart failure. This compensatory response involves the activation of sympathetic tone and the renin-angiotensin-aldosterone (RAA) system, which increases the force of cardiac contraction, vascular resistance, and circulatory volume. However, over time sympathetic activation and neurohumoral changes lead to disease progression and worsening of symptoms. That is why the cornerstone of therapy based on disease-modifying drugs consists of angiotensin-converting enzyme inhibitors (ACEI), beta blockers and mineralocorticoid receptor antagonists. These drugs reduce the mortality, hospitalization risks and the symptoms of the disease. It is recommended that ACEI should be replaced by angiotensin receptor-neprilysin inhibitor (ARNI) in patients who remain symptomatic despite optimal treatment. The biggest innovation in the treatment of HFrEF is the introduction of a fourth drug, the sodium-glucose co-transporter 2 (SGLT2) inhibitor, a non-insulin antidiabetic, which significantly reduces mortality, in all patients regardless of their diabetes status. The diuretic/natriuretic effect of SGLT2 inhibitors may further reduce congestion (without electrolyte disbalance and activation of the RAA system), and the dose of loop diuretics used to relieve symptoms of congestion. Other drugs that can be used to treat HFrEF are vasodilators, digoxin, angiotensin receptor antagonists and ivabradine, and more recently guanylate cyclase stimulator, myosin activator and parenteral iron preparation in case of anemia.